2014
DOI: 10.1097/bpo.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Nerve Monitoring During Percutaneous Pinning of Supracondylar Fractures in Children

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…74 Ulnar nerve location by palpation only is not a totally safe technique. 75 Other techniques such as intra-operative electrical stimulation 76 or ultrasound monitoring 77 have been proposed as safe but technically demanding methods to avoid ulnar nerve injuries.…”
Section: Surgical Techniquementioning
confidence: 99%
“…74 Ulnar nerve location by palpation only is not a totally safe technique. 75 Other techniques such as intra-operative electrical stimulation 76 or ultrasound monitoring 77 have been proposed as safe but technically demanding methods to avoid ulnar nerve injuries.…”
Section: Surgical Techniquementioning
confidence: 99%
“…However, there is slightly probability of radial or anterior interosseous nerve damage associated with lateral pin fixation (Sibinski et al 2006 ; Brauer et al 2007 ). Different surgical techniques were used to prevent iatrogenic ulnar nerve injury (Sibinski et al 2006 ; Bashyal et al 2009 ; Brauer et al 2007 ; Eidelman et al 2007 ; Shim and Lee 2002 ; Skaggs et al 2001 ; Michael and Stanislas 1996 ; Gordon et al 2001 ; Wind et al 2002 ; Shtarker et al 2014 ). However, these techniques do not completely prevent ulnar nerve injuries (Brauer et al 2007 ; Skaggs et al 2001 ; Wind et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…[19] Lyons et al [20] and Kalenderer et al [21] reported 5% and 5.2% iatrogenic ulnar nerve injuries in 375 and 473 patients, respectively. Iobst et al [7] reported nerve injuries in 20 patients (6.6%) they treated with semi-sterile technique.…”
Section: Discussionmentioning
confidence: 99%
“…It is the opinion of the authors that this could be minimalized if mini-open technique described by Green et al [22] is used, but it is inappropriate to use this technique in semi-sterile conditions. Shtarker et al [19] used ulnar nerve monitoring to avoid iatrogenic nerve injury for medial pin insertion and stated that there were no iatrogenic ulnar nerve injuries in 138 patients. Similarly, nerve monitoring is not appropriate for semi-sterile conditions.…”
Section: Discussionmentioning
confidence: 99%